Hume and the enlightenment (Routledge, 2015)
While Hume remains one of the most central figures in modern philosophy his place within Enlightenment thinking is much less clearly defined. Taking recent work on Hume as a starting point, this volume of original essays aims to re-examine and clarify Hume's influence on the thought and values of the Enlightenment.